One day at Horrorland - Stine, R. L. (New York : Scholastic, 2008)
Luke and Lizzy Morris stumble upon Werewolf Village, the Doom Slide, and the Coffin Cruise at HorrorLand, a terrifying amusement park where the Morris family rides and screams as though it is their last time; includes video game tips, secrets from the series, and more.
3.4
5-8
Keywords: Amusement parks -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Amusement parks -- Fiction; Horror fiction; Horror fiction